Effect of diazotrophic bacteria on pineapple Cayenne Champac plantlets with different substrates - Weber, Olmar Baller; Correia, Diva; Silveira, Márcia Regina Souza da; Crisóstomo, Lindbergue Araújo; Oliveira, Edivaldo Marinho de; Sá, Eduardo Gomes (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the effect of a diazotrophic bacteria isolated from pineapple (Ananas comosus) plants on plantlets growth and nutrient accumulation of the cultivar Cayenne Champac grown with different substrates in tubules conditions. Treatments consisted of six substrates: carbonized rice hulls + leave dust from carnauba (Copernicia cerifera) palm tree + vermicompost; carbonized rice hulls + rip coir dust + vermicompost; carbonized rice hulls + vermiculite + vermicompost; carbonized rice hulls + leave dust from carnauba palm tree + vermiculite; carbonized rice hulls + ripe coir dust; and carbonized rice hulls + vermiculite. The bacterium isolate was identified by similarity (97% to 98%) of sequences of 16S rDNA with the species Asaia bogorensis. After the bacterial inoculation, plants were transferred to substrates into tubules conditions. After four months, at harvesting, acclimated plants were ready to be planted in the field. The occurrence of diazotrophic bacteria related to A. bogorensis in pineapple plants is presented here for the first time. The bacterial isolate AB219 promoted higher plant surviving onto tubules conditions, and induced higher root weight with the substrate of carbonized rice hulls, vermiculite and vermicompost. Higher sodium contents were detected in bacterized plants, independently of substrates.